5x(x-1)+3(x-4)=-1

Simple and best practice solution for 5x(x-1)+3(x-4)=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x(x-1)+3(x-4)=-1 equation:



5x(x-1)+3(x-4)=-1
We move all terms to the left:
5x(x-1)+3(x-4)-(-1)=0
We add all the numbers together, and all the variables
5x(x-1)+3(x-4)+1=0
We multiply parentheses
5x^2-5x+3x-12+1=0
We add all the numbers together, and all the variables
5x^2-2x-11=0
a = 5; b = -2; c = -11;
Δ = b2-4ac
Δ = -22-4·5·(-11)
Δ = 224
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{224}=\sqrt{16*14}=\sqrt{16}*\sqrt{14}=4\sqrt{14}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-2)-4\sqrt{14}}{2*5}=\frac{2-4\sqrt{14}}{10} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-2)+4\sqrt{14}}{2*5}=\frac{2+4\sqrt{14}}{10} $

See similar equations:

| -10-8=x | | -10-(-8)=x | | 2x-2000=x | | 8=10*x-2 | | y×150=360 | | 3n÷5=9 | | X+.15x=80000 | | X+2x+(x-4)=36 | | 2(3x+5=-44 | | 4x-8/21=3x+5/14 | | 6+x/2=-1 | | 0.85^x=0.01 | | -(2x-5)+(3x-7)= | | -(2x-5)+(3x-7)=0 | | 6^x-2^x=2^5 | | 4x²+16x-8=0 | | f(6)=f(6-1)+100 | | 25*65/5+x=600 | | 5h-2(h=12) | | 5h-2(h=11) | | X+4x=4.2 | | 4x^2-8x-4x=0 | | 1+2j=-j−4 | | 3x-9÷5=x | | 8a=9a-5 | | 3+2x-(x+4)=x-1 | | 3(x+5=30 | | 5x^2+14x+10=0 | | 40+40+50+x=360 | | x+x/2+x/4=147 | | 3x-4+(3x+16)=180 | | (20-5x)(20+5x)=0 |

Equations solver categories